Does PEEK/HA Enhance Bone Formation Compared With PEEK in a Sheep Cervical Fusion Model?. Issue 11 (November 2016) - Walsh, William R.; Pelletier, Matthew H.; Bertollo, Nicky; Christou, Chris; Tan, Chris
Abstract: Background: Polyetheretherketone (PEEK) has a wide range of clinical applications but does not directly bond to bone. Bulk incorporation of osteoconductive materials including hydroxyapatite (HA) into the PEEK matrix is a potential solution to address the formation of a fibrous tissue layer between PEEK and bone and has not been tested. Questions/purposes: Using in vivo ovine animal models, we asked: (1) Does PEEK‐HA improve cortical and cancellous bone ongrowth compared with PEEK? (2) Does PEEK‐HA improve bone ongrowth and fusion outcome in a more challenging functional ovine cervical fusion model? Methods: The in vivo responses of PEEK‐HA Enhanced and PEEK‐OPTIMA ® Natural were evaluated for bone ongrowth in the form of dowels implanted in the cancellous and cortical bone of adult sheep and examined at 4 and 12 weeks as well as interbody cervical fusion at 6, 12, and 26 weeks. The bone‐implant interface was evaluated with radiographic and histologic endpoints for a qualitative assessment of direct bone contact of an intervening fibrous tissue later. Gamma‐irradiated cortical allograft cages were evaluated as well. Results: Incorporating HA into the PEEK matrix resulted in more direct bone apposition as opposed to the fibrous tissue interface with PEEK alone in the bone ongrowth as well as interbody cervical fusions. No adverse reactions were found at the implant‐bone interface for either material. Radiography and histology revealed resorption and fracture of the allograft devices in vivo. Conclusions: Incorporating HA into PEEK provides a more favorable environment than PEEK alone for bone ongrowth. Cervical fusion was improved with PEEK‐HA compared with PEEK alone as well as allograft bone interbody devices. Clinical Relevance: Improving the bone‐implant interface with a PEEK device by incorporating HA may improve interbody fusion results and requires further clinical studies.